Factors influencing the use of thromboprophylaxis in cancer outpatients in clinical practice: A prospective study. Issue 6 (December 2015) - Panizo, Elena; Alfonso, Ana; García-Mouriz, Alberto; López-Picazo, José M.; Gil-Bazo, Ignacio; Hermida, José; Páramo, José A.; Lecumberri, Ramón
Abstract: Introduction: Current clinical practice guidelines do not recommend routine pharmacological thromboprophylaxis in cancer outpatients receiving chemotherapy. However, a high proportion of cancer-associated venous thromboembolism (VTE) events occur in this setting. There are scarce data on the use of thromboprophylaxis in ambulatory cancer patients in real clinical practice. Material and methods: We conducted a single-center prospective study aimed to evaluate the use and factors influencing pharmacological prophylaxis in consecutive cancer patients receiving ambulatory chemotherapy. Patients were followed for 90 days after inclusion. Results: A total of 1108 patients were included. According to the Khorana score, 45.8% patients were classified as low-risk, 47.4% intermediate-risk and 6.8% as high-risk. Outpatient pharmacological prophylaxis was administered at any time during follow-up to 157 patients (14.2%) with a median duration of 42 days (range 1–90). Main factors influencing thromboprophylaxis were: previous history of VTE (odds ratio [OR], 19.11; 95% CI, 9.61–37.98), intercurrent hospitalization (OR, 5.40; 95% CI, 3.57–8.16), and gastrointestinal or gynecologic cancer (OR, 1.76; 95% CI, 1.11–2.80 and OR, 2.34; 95% CI, 1.05–5.26, respectively). During follow-up 58 (5.2%) VTE events were observed. Independent predictors of VTE were the site of malignancy (OR, 3.04; 95%CI, 1.20–7.71 and OR, 2.47; 95%CI, 1.21–5.01 for pancreas and lung cancer, respectively) and previous VTE (OR, 4.23; 95%CI, 1.26–14.27). Outpatient prophylaxis was associated with a lower risk of VTE during follow-up (OR, 0.30; 95%CI, 0.10–0.95). Conclusions: Although the type of malignancy appears as the most relevant variable for decision-making, additional efforts are required to identify patients at particular high thrombosis risk. Highlights: The incidence of VTE in cancer outpatients is not negligible. Most cancer outpatients do not received pharmacologic thromboprophylaxis. Cancer type and previous VTE seem the most relevant variables for decision-making. In clinical practice, thromboprophylaxis use is influenced by other factors.